Linking photorespiration, monoterpenes and thermotolerance in Quercus (New Phytologist, 2002)
* • The functions of two important plant processes, photorespiration and monoterpene production remain controversial. Here, we investigated one possible function, that of protection of plants from photodamage at high temperatures. * • Fluorescence, reflectance, monoterpene concentrations and visual leaf damage were measured in Quercus ilex seedlings exposed to temperature increases from 25 to 50°C (in 5°C steps) under photorespiratory (21% O 2 ) or nonphotorespiratory (2% O 2 ) atmospheres, and under control or terpene fumigation conditions. * • Lower variable to maximum fluorescence ratio (Fv : Fm: potential photochemical efficiency of photosystem II, PSII) and electron transport rate (ETR) were found in nonphotorespiratory conditions at temperatures greater than 35°C. Monoterpene concentrations were also lower, and leaf damage greater, in the low O 2 atmospheres. Monoterpene fumigation, which increased the foliar terpene concentrations by two- to four-fold, increased the photochemical efficiency between 35°C and 50°C, and decreased leaf damage, only under the nonphotorespiratory conditions. * • These results provide evidence that: photorespiration decreases photodamage, especially at high temperatures; photorespiration increases monoterpene production; plants are able to acquire exogenous monoterpenes and the acquisition response to temperature follows the stomatal conductance response; and monoterpenes can replace photorespiration in protection from photodamage at high temperatures, possibly by scavenging oxygen-reactive species, but they do not provide additional thermotolerance.